Economic Growth in Guinea and How to Accelerate It - Mijiyawa, Abdoul Ganiou (World Bank, Washington, DC, 2017)
This paper addresses two main questions: (1) What are the binding constraints to Guinea's economic growth? and (2) What would it take to accelerate growth in the country? Using the growth diagnostic approach, the paper finds three binding constraints to growth: (i) lack of good infrastructure (roads and electricity), (ii) low access to finance, and (iii) poor governance. Simulation results highlight the need for total factor productivity growth for higher gross domestic product growth rates over the medium term. Specifically, Guinea needs 1 to 2 percent total factor productivity growth to maintain 5 to 7 percent gross domestic product growth, with a 16 to 21 percent investment rate by 2020. The lower bound of the range of the investment rate is similar to Guinea's experience in the past decade; the upper bound is slightly superior to the country's recent performance. The paper discusses some of the policy options to consider to address the key binding constraints to economic growth as well as to overcome the challenge of increasing total factor productivity growth in Guinea.